The Role of Village Funds in Alleviating Poverty in The Nias Islands - Berutu, Saiful Ragatna; Syafii, M. (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
Poverty is a classic problem experienced by every country in the world, including Indonesia. In 2023, the highest percentage of poor people in North Sumatra Province was in the Nias Islands, namely West Nias Regency (22.81%), North Nias Regency (21.79%), South Nias Regency (16.39%), Nias Regency (15.10%), and Gunungsitoli City (14.78%). This figure is far greater than the percentage of poor people in North Sumatra Province at 8.15%.This study aims to determine the role of the Village Fund in alleviating Poverty in the Nias Islands. Researchers used panel data regression with the Village Fund as the main independent variable coupled with the Human Development Index and Economic Growth variables to be able to produce a more accurate regression equation model to explain Poverty in Nias Islands. The results showed that village funds had a negative and significant effect on poverty. In line with the research results and also regulatory support from the government related to allocating the village fund budget based on the poverty rate, the role of village funds in alleviating poverty in the Nias Islands is very important and needed. For this reason, the government should continue the village fund program to accelerate poverty reduction in villages, especially in the Nias Islands.